1986
DOI: 10.1038/sc.1986.14
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an arm ergometer training programme on wheelchair subjects

Abstract: SummaryThe purpose of the present investigation was to study the effects of an arm ergometer training programme on several physiological variables of recreational wheelchair subjects. Ten paraplegics (5 experimental, S control) were tested prior to and im mediately after a 2 month exercise regimen at 80% of peak heart rate (30 min per day,S days per week,for 8 consecutive weeks at 50 rev/min). The results demonstrated significant increases (P < 0·05) in V0 2 max (J min -1 & ml kg-1 min-I) and work load but onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 10 publications
0
24
2
1
Order By: Relevance
“…(3) PeakV/02 of com petitors was reduced during the off season. There are a lot of reports concerning the effects of training on the improvement of physical fitness of subjects (Saltin et al 1968;Ekblom et al, 1968;Taylor et al, 1986). Two significant differences appear in our study.…”
Section: Discussioncontrasting
confidence: 42%
“…(3) PeakV/02 of com petitors was reduced during the off season. There are a lot of reports concerning the effects of training on the improvement of physical fitness of subjects (Saltin et al 1968;Ekblom et al, 1968;Taylor et al, 1986). Two significant differences appear in our study.…”
Section: Discussioncontrasting
confidence: 42%
“…Changes in aerobic capacity are associated with parallel changes in mitochondrial density and capillarity of skeletal muscles. 25 Also, Taylor et al 26,27 observed a signi®cant increase in slow twitch areas after endurance arm exercise training in SCI subjects, and it supported in faster V . O 2 kinetics in the trained SCI subjects.…”
Section: Steadymentioning
confidence: 95%
“…The key findings from these three trials were that ES-driven exercise (versus no intervention) of the paralyzed lower limbs increased lower limb lean body mass; 17 strength and fitness training (versus education and relaxation) decreased pain; 19 and arm-cranking exercise (versus no intervention) increased the proportion of slow twitch muscle fibres in the triceps muscles. 22 The size of the between-group differences could not be ascertained in the other three trials with statistically significant between-group differences. 18,20,21 (2) Gait training: Five trials assessed the effectiveness of gait training either with weight-supported systems 23,24,27 or with orthoses.…”
Section: La Harvey Et Almentioning
confidence: 89%
“…23,[31][32][33]35,37 Dropouts were also a common problem, with only 18 trials reporting outcome data on at least 85% of subjects. 8,9,[18][19][20][22][23][24]27,28,[31][32][33][34][35]37,40,41 Not surprisingly and due to the nature of the interventions, only two trials blinded subjects 37,43 and no trial blinded therapists. Figure 1 Examples of outcomes from trials demonstrating the four types of results, namely, between-group statistical significance and clearly important treatment effects; between-group statistical significance and inconclusive treatment effects; no between-group statistical significance and inconclusive treatment effects; and no between-group statistical significance and ineffective treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation